Unveiling the Invisible Impact: Exploring Musculoskeletal Symptoms in Healthcare Students Post COVID-19 Infection. A Cross-Sectional Study in Jordan - Bani Monia, Odai; Abu Zalam, Mohammad; AlAmour, Bashar; Mohammad, Ahmad; AlSamhori, Jehad; AlTarifi, Leen; AlHunaifat, Jood; Al-Hadidi, Fadi (Jordan Medical Journal, 2025)
Background and Aims: Recent studies found a lot of COVID-19 patients reporting persistent musculoskeletal symptoms after recovering from the acute infection. This study assessed musculoskeletal symptoms in young individuals in Jordan three months after mild to moderate COVID-19 infection, examining the impact of gender and other factors due to a lack of regional research on post-acute COVID-19 complications. Materials and Methods Methods: We conducted a cross-sectional study from November 2022 to December 2022, using an online questionnaire on Google Forms distributed to university healthcare students via social media. The questionnaire assessed demographics, COVID-19 symptoms including musculoskeletal symptoms, and their association with patient characteristics and disease course. Results: 261 students, comprising 177 (67.8%) females and 84 (32.2%) males with a mean age of 21.41, participated in our research. 21.4% of our participants complained of at least one musculoskeletal symptom after the acute phase of COVID-19 infection, among which fatigue was the most common (71.6%) followed by headache (60.9%) and muscle pain (52.5%). Female gender was found to be significantly associated with a higher risk of developing musculoskeletal symptoms after the acute phase of COVID-19 infection. Conclusion: The current study found that many young people who recovered from COVID-19 continue to experience musculoskeletal complaints, which could impact their daily activities and contribute to the burden of the disease. There is a higher prevalence of back pain and joint pain complaints in females, which requires further investigation. Cohort studies may help to better understand the relationship between COVID-19 and ongoing musculoskeletal problems.